Sorafenib Repurposing for Ophthalmic Delivery by Lipid Nanoparticles: A Preliminary Study - Angela Bonaccorso; Veronica Pepe; Cristina Zappulla; Cinzia Cimino; Angelo Pricoco; Giovanni Puglisi; Francesco Giuliano; Rosario Pignatello; Claudia Carbone (Pharmaceutics, 2021)
Uveal melanoma is the second most common melanoma and the most common intraocular malignant tumour of the eye. Among various treatments currently studied, Sorafenib was also proposed as a promising drug, often administered with other compounds in order to avoid resistance mechanisms. Despite its promising cellular activities, the use of Sorafenib by oral administration is limited by its severe side effects and the difficulty to reach the target. The encapsulation into drug delivery systems represents an interesting strategy to overcome these limits. In this study, different lipid nanoparticulate formulations were prepared and compared in order to select the most suitable for the encapsulation of Sorafenib. In particular, two solid lipids (Softisan or Suppocire) at different concentrations were used to produce solid lipid nanoparticles, demonstrating that higher amounts were able to achieve smaller particle sizes, higher homogeneity, and longer physical stability. The selected formulations, which demonstrated to be biocompatible on Statens Seruminstitut Rabbit Cornea cells, were modified to improve their mucoadhesion, evaluating the effect of two monovalent cationic lipids with two lipophilic chains. Sorafenib encapsulation allowed obtaining a sustained and prolonged drug release, thus confirming the potential use of the developed strategy to topically administer Sorafenib in the treatment of uveal melanoma.